OS04.6 DCE-MRI perfusion predicts pseudoprogression in metastatic melanoma treated with immunotherapy. (19th April 2017) - Umemura, Y.; Wang, D.; Peck, K.; Shi, W.; Zhang, Z.; Fatovic, R.; Anderson, E.; Beal, K.; Kaley, T.; Young, R.
Abstract: Objective: To assess the ability of dynamic contrast enhanced T1 magnetic resonance imaging (DCE-MRI) to identify pseudoprogression in melanoma brain metastases. BACKGROUND: Immunotherapy is the emerging standard of care for metastatic melanoma. Pseudoprogression is the transient worsening of enhancing lesions that can result from activated tumor directed immunity, and may be misclassified as progression. We hypothesize DCE-MRI can be applied to identify pseudoprogression in patients with melanoma brain metastases. METHODS: Retrospectively, 44 patients with melanoma brain metastases were identified to have received immunotherapy and DCE-MRI from 1/2011 to 6/2016 at Memorial Sloan Kettering Cancer Center. We analyzed total of 64 enhancing lesions ≥ 5 mm diameter, new or increased while on immunotherapy. Lesion classification was determined by histopathology, or by follow up with pseudoprogression defined as neurological and radiographic stability or improvement without any new treatment for ≥ 2 months. Results: Most patients received ipilimumab monotherapy (64%). The median duration of immunotherapy was 9 weeks (range 0–138). Histopathology was available in 13/55 progression and 1/9 pseudoprogression lesions. Twelve progression and 8 pseudoprogression lesions were previously irradiated. Fourty-four progression lesions and 8 pseudoprogression lesions were hemorrhagic. The median lesion volume was not statistically different between the pseudoprogression group at 2.3cm3 and the progression group at 3.2cm3 (p=0.82). The median 90%tile plasma volume (Vp90) was smaller in pseudoprogression at 2.2cm3 than in POD at 5.3cm3 (p=0.02), and it remained significant after false discovery rate adjustment (p=0.04). Conclusions: We found that pseudoprogression has significantly lower Vp90 on DCE-MRI compared to progression, which can be useful in radiographic follow up of brain metastases in melanoma patients receiving immunotherapy. Better differentiation of pseudoprogression and progression is needed to provide appropriate clinical interventions in these patients. STUDY SUPPORT: Diane Wang was supported by the Memorial Sloan Kettering Cancer Center Medical Student Summer Fellowship. This work was partially supported by NIH Core Grant P30 CA008748.